Molecular cloning, sequence analysis, and expression of the gene encoding the immunodominant 32-kilodalton protein of Cowdria ruminantium. - van Vliet, A H (1994)
Cowdria ruminatium, the causative agent of heartwater disease, expresses an immunodominant and conserved 32-kilodalton protein (MAP1; formerly called Cr32), which is currently in use for serodiagnosis of the disease. The gene encoding this protein, designated map1, was detected, cloned, and characterized. The gene is conserved between four different stocks of C. ruminantium originating from Senegal, Sudan, South Africa, and Zimbabwe. Homology searches revealed MAP1 to be homologous to the Anaplasma marginale surface protein MSP4, a potential protective antigen. The MAP1 protein, expressed in Escherichia coli fused with glutathione S-transferase, is specifically recognized by sera from animals infected with seven different stocks of C. ruminantium.